Value realization of intelligent emergency management: research framework from technology enabling to value creation - Yan Guo; Yan Song; Mingyue Zhang (Data Science and Management)
This study investigated the application and the application value of intelligent emergency in emergency management in the big data environment. It addresses the neglect of the application value (performance) measurement of intelligent emergency, further improving the effectiveness of intelligent emergency management. First, approximately 3900 documents from the intelligent emergency field are analyzed to determine the future research trend in intelligent emergency management. The socio-technical theory concerning technical and social systems is introduced. The emergency management system concepts of “technology enabling” and “enabling value creation” are defined according to bibliometric analysis and socio-technical theory. Second, a research framework that includes technology enabling and enabling value creation for the decision-making paradigm in emergency management according to the big data environment is constructed. A detailed analysis approach from intelligent emergency technology enabling to enabling value creation in emergency management is proposed. Finally, earthquake disasters are taken as examples, and specific analyses of the intelligent emergency enabling and enabling value creation are explored; enabling value creation is discussed based on measurable indicators. The clear concept of emergency management system technology enabling and enabling value creation, as well as the detailed analysis approach from intelligent emergency technology enabling to enabling value creation, provide a theoretical bases for scholars and practitioners to evaluate the value (performance) of intelligent emergency for the first time.